Effect of supportive periodontal therapy on tooth loss in regular and irregular compliant smokers and non-smokers: A Systematic Review - Roudy KHAYAT; Jean-Marie MEGARBANE; Abdel Rahman KASSIR; Nadim MOKBEL (International Arab Journal of Dentistry (IAJD), 2023)
Aim: The aim of this systematic review is to analyze and compare tooth loss (TL) rates between regular and irregular compliant patients having different smoking habits.Materials and Methods: Electronic and manual literature searches were conducted by one author in several databases, including Medline (PubMed), Embase, Google Scholar. A total of 156 publications were screened. Three reviewers analyzed the articles and extracted the data. A total of 33 studies met the inclusion criteria.Results: A total of 30 articles were eligible for qualitative analysis, and only 3 for quantitative analysis. Compliance and smoking case definition as well as recall intervals during supportive periodontal therapy (SPT) differed widely between studies. A total of 10 publications reported significant differences in TL rates between regular (RC) and irregular compliant (IC) patients, while 25 publications reported significant differences in TL rates between smokers and non-smokers.Conclusion: Regular attendance to SPT visits and non-smoking patients are associated with fewer TL rates. Smoking is considered a major modifiable risk factor for TL.